Faktor-faktor yang mempengaruhi minat remaja menabung di bank syariah dengan pengetahuan sebagai variabel intervening - Putri, Ayu; Setiawan, Ari (Journal of Management and Digital Business, 2022)
This study analyzed the effect of religiosity, income, and promotions on the intention to save, with knowledge as an intervening variable. This quantitative research focuses on the population of the people in Medayu Village. The sample in this study used a purposive sampling technique, namely 100 respondents from Garuda youth in Medayu Village. The analysis tool uses path analysis. The results showed that income, promotion, and knowledge positively affected the intention to save. Religiosity does not affect the intention to save. Religiosity, income, and promotion have a positive effect on knowledge. Knowledge can mediate the influence of religiosity, income, and promotions on the intention to save.